The ubiquitin proteasome system acutely regulates presynaptic protein turnover and synaptic efficacy. - Speese, S.D.; Trotta, N.; Rodesch, C.K.; Aravamudan, B.; Broadie, K. (Current Biology, 2003)
The ubiquitin proteasome system (UPS) mediates regulated protein degradation and provides a mechanism for closely controlling protein abundance in spatially restricted domains within cells. We hypothesized that the UPS may acutely determine the local concentration of key regulatory proteins at neuronal synapses as a means for locally modulating synaptic efficacy and the strength of neurotransmission communication.We investigated this hypothesis at the Drosophila neuromuscular synapse by using an array of genetic and pharmacological tools. This study demonstrates that UPS components are present in presynaptic boutons and that the UPS functions locally in the presynaptic compartment to rapidly eliminate a conditional transgenic reporter of proteasome activity. We assayed a panel of synaptic proteins to determine whether the UPS acutely regulates the local abundance of native synaptic targets. Both acute pharmacological inhibition of the proteasome (<1 hr) and targeted genetic perturbation of proteasome function in the presynaptic neuron cause the specific accumulation of the essential synaptic vesicle-priming protein DUNC-13. Most importantly, acute pharmacological inhibition of the proteasome (<1 hr) causes a rapid strengthening of neurotransmission (an approximately 50% increase in evoked amplitude) because of increased presynaptic efficacy. The proteasome-dependent regulation of presynaptic protein abundance, both of the exogenous reporter and native DUNC-13, and the modulation of presynaptic neurotransmitter release occur on an intermediate, rapid (tens of minutes) timescale.Taken together, these studies demonstrate that the UPS functions locally within synaptic boutons to acutely control levels of presynaptic protein and that the rate of UPS-dependent protein degradation is a primary determinant of neurotransmission strength.